Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

SNAPSHOT USA 2024: Year 6 of the Coordinated National Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Daniel J. Herrera; Camilla Price; Phuong‐Thao Nguyen‐Nu; Katrina Adamczyk; Peter D. Alexander; David Allen; Jesse M. Alston; Diego F. Alvarado‐Serrano; et al. (Global Ecology and Biogeography, 2026)
Motivation SNAPSHOT USA is an annual, multi‐contributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2024 contains 377,427 records of camera trap image sequence data and 3127 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in 49 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1 August and 19 December in 2024. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2024 comprises two .csv files. The original data can be found within the SNAPSHOT USA 2024 project on the Wildlife Insights platform.

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Subtropical coral expansion into SE Australia: a haven for both temperate and expatriating tropical reef fishes - Max J. O’Connell; Ashley M. Fowler; Sam J. Allan; Giglia A. Beretta; David J. Booth (Coral Reefs, 2023)
We examined reef fish assemblages in and adjacent to a newly established coral bed (subtropical Pocillopora aliciae ) in temperate south-eastern Australia, to understand whether novel coral habitat is facilitating assemblages of range-expanding tropical and local temperate fishes. This is the first comprehensive assessment of fish species associating with this novel coral habitat within a temperate environment. Twenty fish species were observed associating with the coral (8 tropical and 12 temperate). Both temperate and tropical species were observed at greater (up to 48 times higher) densities on the coral than on nearby temperate rocky reef in the area, suggesting that the corals generally concentrate fish and may aid in tropicalisation for species that use subtropical coral as habitat. Future research should investigate the ongoing expansion of this coral, the relative quality of coral habitat for fish in temperate regions and the potential implications for functioning of temperate rocky reef ecosystems.

Heritage genetics for adaptation to marginal soils in barley - Sidsel Birkelund Schmidt; Lawrie K. Brown; Allan Booth; John Wishart; Pete E. Hedley; Peter Martin; Søren Husted; Timothy S. George; Joanne Russell (Trends in Plant Science, 2023)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Recruiting a long way from home: Domino damselfish Dascyllus trimaculatus can detect new temperate coral habitat and conspecifics - Max J. O'Connell; Ashley M. Fowler; Sam J. Allan; Giglia A. Beretta; David J. Booth (Journal of Fish Biology, 2022)
Climate change is driving tropicalisation of temperate reefs, yet it is unclear how range‐shifting tropical fishes locate suitable habitat. The authors tested whether juvenile tropical damsels Dascyllus trimaculatus could detect rare coral habitat ( Pocillopora aliciae ) and conspecifics on temperate rocky reefs using olfactory and visual preference experiments. For all cues, individuals selected and spent more time than expected in aquarium areas with the cue present, which included coral odour and conspecific odour and visual cues. This indicates that vagrant coral‐reef fish can detect rare suitable habitat outside of their natal range.

Searching for seadragons: predicting micro‐habitat use for the common (weedy) seadragon ( Phyllopteryx taeniolatus ) based on habitat and prey - Sam J. Allan; Max J. O'Connell; David Harasti; O. Selma Klanten; David J. Booth (Journal of Fish Biology, 2022)
Habitat associations can be critical predictors of larger‐scale organism distributions and range shifts. Here the authors consider how a critical habitat, kelp ( Ecklonia radiata ) and prey (mysid crustacean swarms), can influence small‐ and large‐scale distribution on the iconic common (weedy) seadragon ( Phyllopteryx taeniolatus :Syngnathidae). P. taeniolatus are charismatic fish endemic to the temperate reefs of southern Australia, reported to range from Geraldton, Western Australia (28.7667°S, 114.6167°E) around southern Australia to Port Stephens, New South Wales (32.614369°S, 152.325676°E). The authors test a previously developed model of seadragon habitat preferences to predict P. taeniolatus occurrence within four sites from Sydney to the northern limit of their range in eastern Australia. They determined that P. taeniolatus associations with Ecklonia and mysid shrimp can be extrapolated across multiple sites to predict the occurrence of individual P. taeniolatus within a location/site. For instance, the authors demonstrated a significant positive relationship between the density of mysid swarms and the density of P. taeniolatus , evident across all sites despite large differences in the density of mysid swarms among sites. The findings are the first to model P. taeniolatus habitat associations across multiple sites to the northern limit of their range and have applications in protecting P. taeniolatus populations and how they may respond under climate change scenarios, such as poleward kelp retractions.

Space use by the endemic common (weedy) seadragon ( Phyllopteryx taeniolatus ): influence of habitat and prey - Sam J. Allan; Max J. O'Connell; David Harasti; O. Selma Klanten; David J. Booth (Journal of Fish Biology, 2022)
The weedy seadragon ( Phyllopteryx taeniolatus : Syngnathidae) is an iconic fish endemic to the southern coastal waters of Australia. The authors of this study analysed the habitat preferences and factors influencing microhabitat selection by P. taeniolatus in a population from Kurnell, NSW, Australia. Using field surveys and the resource selection probability function, the authors determined that P. taeniolatus significantly preferred kelp ( Ecklonia radiata ) – dominated habitat and avoided rock‐dominated habitat. They showed P. taeniolatus preferred habitat of between 40% and 80% coverage of Ecklonia , while avoiding areas of P. taeniolatus habitat selection. The strong dependence of P. taeniolatus on Ecklonia habitat shown in this study was previously untested and highlights that reductions in Ecklonia cover under climate change, or impacts from increasing urbanisation, may render seadragon populations vulnerable to declines.

Association mapping of malting quality traits in UK spring and winter barley cultivar collections - Mark E. Looseley; Luke Ramsay; Hazel Bull; J. Stuart Swanston; Paul D. Shaw; Malcolm Macaulay; Allan Booth; Joanne R. Russell; Robbie Waugh; William T. B. Thomas (Theoretical and Applied Genetics, 2020)
Key message Historical malting quality data was collated from UK national and recommended list trial data and used in a GWAS. 25 QTL were identified, with the majority from spring barley cultivar sets. Abstract In Europe, the most economically significant use of barley is the production of malt for use in the brewing and distilling industries. As such, selection for traits related to malting quality is of great commercial interest. In order to study the genetic basis of variation for malting quality traits in UK cultivars, a historical set of trial data was collated from national and recommended list trials from the period 1988 to 2016. This data was used to estimate variety means for 20 quality related traits in 451 spring barley cultivars, and 407 winter cultivars. Genotypes for these cultivars were generated using iSelect 9k and 50k genotyping platforms, and a genome wide association scan performed to identify malting quality quantitative trait loci (QTL). 24 QTL were identified in spring barley cultivars, and 2 from the winter set. A number of these correspond to known malting quality related genes but the remainder represents novel genetic variation that is accessible to breeders for the genetic improvement of new cultivars.

Resistance to Rhynchosporium commune in a collection of European spring barley germplasm - Mark E. Looseley; Lucie L. Griffe; Bianca Büttner; Kathryn M. Wright; Jill Middlefell-Williams; Hazel Bull; Paul D. Shaw; Malcolm Macaulay; Allan Booth; Günther Schweizer; Joanne R. Russell; Robbie Waugh; et al. (Theoretical and Applied Genetics, 2018)

Influence of poultry meal, meat meal or soybean meal inclusion on weight gain and production characteristics of Australian snapper Pagrus auratus - M. A. Booth; G. L. Allan; A. J. Anderson (Aquaculture International, 2012)

Protein and energy utilization and the requirements for maintenance in juvenile mulloway (Argyrosomus japonicus) - Igor Pirozzi; Mark A. Booth; Geoff L. Allan (Fish Physiology and Biochemistry, 2010)

Genome-wide SNP discovery and linkage analysis in barley based on genes responsive to abiotic stress - Nils Rostoks; Sharon Mudie; Linda Cardle; Joanne Russell; Luke Ramsay; Allan Booth; Jan T. Svensson; Steve I. Wanamaker; Harkamal Walia; Edmundo M. Rodriguez; Peter E. Hedley; Hui Liu; et al. (Molecular Genetics and Genomics, 2005)